1996
DOI: 10.1377/hlthaff.15.1.152
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Employment Trends in California, 1982-1994

Abstract: During the 1980s California hospitals responded to selective contracting, growth in managed care, and the Medicare prospective payment system (PPS) by controlling their level of spending. This DataWatch examines whether these hospitals achieved these savings by changing the number and/or the mix of hospital employees. We examined employment trends because wages represent the largest component of hospital budgets and because the number and mix of personnel can be changed in the short run. Analysis of the Califo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…While there has been a great deal of interest in the effect of nurse staffing levels on the quality of care in hospitals, there has been much less interest in determining the factors that affect the nurse staffing levels other than documenting the changes during the health care crisis of the past 15 years (Aiken, Sochalski, and Anderson 1996;Anderson and Kohn 1996;Spetz 1998;Buerhaus and Staiger 1999;Bond and Raehl 2000;Unruh 2002). Recent work has established that the supply of nurses is not meeting the demand for nurses and that this shortage will worsen in the decades to come (U.S. DHHS 2002).…”
mentioning
confidence: 99%
“…While there has been a great deal of interest in the effect of nurse staffing levels on the quality of care in hospitals, there has been much less interest in determining the factors that affect the nurse staffing levels other than documenting the changes during the health care crisis of the past 15 years (Aiken, Sochalski, and Anderson 1996;Anderson and Kohn 1996;Spetz 1998;Buerhaus and Staiger 1999;Bond and Raehl 2000;Unruh 2002). Recent work has established that the supply of nurses is not meeting the demand for nurses and that this shortage will worsen in the decades to come (U.S. DHHS 2002).…”
mentioning
confidence: 99%
“…National and statewide assessments of hospital nurse staffing frequently utilize a measure that averages counts of the number of nurses or hours of nursing care given the number of patients or patient days of care per hospital (Aiken, Sochalski, and Anderson 1996; Anderson and Kohn 1996; Spetz 1998; Buerhaus and Staiger 1999; Kovner, Jones, and Gergen 2000; Unruh 2002). These calculations provide a rough measure of nursing staff resources given patient volume, but they do not consider the intensity of nursing care that must be provided for that patient volume.…”
mentioning
confidence: 99%
“…All the studies find RN staffing stable or increasing. [11][12][13][14][15][16] However, research examining the relationship between nurse staffing and the quality of care increasingly finds that better RN staffing correlates with higher quality. Initially, only three 17-19 out of eight 17-24 studies found RN staffing to have a statistically significant negative relationship with patient mortality.…”
mentioning
confidence: 99%